Determination of candidate biomarkers through differential interactome in colorectal adenocarcinoma - TURANLI, BESTE; ÖZBEK SARICA, PEMRA; YILMAZ, BETÜL; ARĞA, KAZIM YALÇIN (My University, 2019)
Colorectal cancer is one of the most lethal types of cancers common in both men and women. According to the data base published by the International Agency for Research on Cancer, colorectal cancer is the third most common type of cancer found in Turkey and worldwide [1]. The high heterogeneity of colorectal cancer leads to difficulties explaining the biology and behavior of this cancer. The aim of this study is to identify prognostic biomarkers and potential therapeutics for colorectal cancer using the protein interactions differentiated among healthy and tumor groups. Among this purpose at first stage, the differential protein-protein interactions (dPPIs) were identified by using “Differential Interactome” algorithm[2] which is published by our research group. Two independent data sets were obtained from “The Cancer Genome Atlas (TCGA)” containing 644 tumor samples and 51 normal samples and “Gene Expression Omnibus (GEO)” containing 32 tumor samples and 32 normal samples. As a result of differential interactome analysis, significant dPPIs were determined (2434 dPPIs in GEO data set, 1619 dPPIs in TCGA data set) and highly interacting protein modules were identified. Principal Component Analysis for diagnostic purpose and Kaplan-Meier analysis for prognostic purpose were performed for each module. 16 modules were determined significant having diagnostic potential while 6 modules were found having prognostic potential. In addition common significant dPPIs in both data sets were observed in point of drug repositioning and 6 dPPIs and 13 drug targets for these interactions were identified. By using molecular dynamics simulations root mean square deviation (RMSD) and root mean square fluctuation were taken as performance metrics to perform further investigation in vitro cell culture. This study will shed light on the identification of specific biomarkers and drug targets for early detection, disease progression, and accurate treatment, helping to understand some systems of colorectal cancer by preventing high mortality.
Keywords: Cancer; Differential Interactome; Molecular Dynamics